Pensamento Algébrico nos Anos Iniciais do Ensino Fundamental nos trabalhos acadêmicos produzidos no Brasil nas últimas três décadas - Oliveira, Tchierly Juliani Bier de (2022)
The present study, with a qualitative and bibliographic approach, intends to investigate understandings about algebraic thinking and propositions related to teaching and learning actions in academic productions produced in Brazil in the last three decades (1990-2020). The objective is to answer the following questions: What treatment has algebraic thinking in Brazil been receiving in recent decades in academic productions? What is shown in relation to the proposition of teaching actions on algebra in the early years of schooling? The corpus of analysis consisted of 29 works, nine theses and twenty dissertations, which were obtained by digital means, from the following bases: Bank of theses and dissertations of the Coordination for the Improvement of Higher Education Personnel - CAPES and the Library Brazilian Digital of Theses and Dissertations – BDTD. After a thorough reading of the theses and dissertations that are part of the corpus of analysis, the general data of the works were analyzed, such as author, advisor, institution, type of work, year of defense and cited authors, which deal with the development of algebraic thinking and later, excerpts from the texts were removed, the analysis units and categories were organized, which are four: Characteristics of algebraic thinking, Student learning, Development of Algebra Teaching Actions and Teacher Training. From the analysis of the works, it is possible to affirm that there is no consensus on what their characteristics of algebraic thinking are, and this occurs both in the theses and dissertations analyzed, as in the texts of the reference authors on the subject. It is evident that there are several characterizations for the ways of producing meanings for the objects and processes of algebra and for those who organize algebraic thinking, there is no unit on which contents/concepts should be learned by students. There are some possibilities to develop them in the relations of regularities, variation and modeling and in the association of algebra with arithmetic. The researchers approach and share the idea that algebraic thinking can be developed from the early years of schooling, long before students' contact with formal algebraic language. Regarding propositions related to teaching actions, research has shown that it is possible to link work with algebraic thinking to the ability to make generalizations, to observe regularities in sequences and numerical patterns. It is expected to encourage among teachers the study and the effectiveness of work on the subject in the classroom, contributing to the teaching and learning process to be significant in terms of the development of algebraic thinking.